2017
DOI: 10.20961/jpscr.v2i01.5240
|View full text |Cite
|
Sign up to set email alerts
|

Study of Antibiotic Use on Pneumonia Patient in Surakarta Referral Hospital

Abstract: <p>Pneumonia is lung inflammation, mostly caused by bacteria. Antibiotics are the primary therapy in cases of pneumonia due to bacteria. This study aimed to determine the profiles of pneumonia patients and their use of antibioticsin Surakarta referral hospital.Data were collected retrospectively by using patient's medical recordand prescription on 2014-2015. Subject were obtained by purposive sampling. Patients diagnosed  pneumonia with antibiotik  therapywere included while patient with comorbide other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
1
5
0
4
Order By: Relevance
“…The results of this study showed that the incidence of pneumonia was higher in males than in females. The finding of this study is in accordance with that from the previous study, where most patients were males [11]. The reason for this is that males are more exposed to greater tendencies of smoking and liquors, which are the CAP risk factors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study showed that the incidence of pneumonia was higher in males than in females. The finding of this study is in accordance with that from the previous study, where most patients were males [11]. The reason for this is that males are more exposed to greater tendencies of smoking and liquors, which are the CAP risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…Smoking habit in healthy adults can increase the risk of lung disease and become the etiology of bronchitis and pneumonia [10]. Other risk factors that can cause pneumonia are low socio-economic status, low nutritional status, low healthcare accessibility, unjust medical practices, and chronic disease sufferer [11].…”
Section: Discussionmentioning
confidence: 99%
“…Lama perawatan merupakan salah satu faktor yang dapat digunakan untuk mengukur tingkat efektivitas penggunaan obat (Farida, Trisna, & Nur, 2017) (Farida, Putri, Hanafi, & Herdianti, 2020…”
Section: Karakteristik Pasienunclassified
“…Akan tetapi pada pneumonia yang disebabkan oleh Pseudomonas aeruginosa menunjukan telah resisten terhadap Ceftriaxon, sedangkan bakteri lain seperti Klabsiella pneumonia masih menunjukan sensitivitas sebesar 33,33% (Farida, Puspita, & Yusvida, 2019). Studi di rumah sakit rujukan daerah Surakarta menyebutkan bahwa Ceftriaxon juga merupakan antibiotik empirik yang paling banyak di resepkan pada pasien pneumonia dewasa (Farida, Trisna, & Nur, 2017). Studi lain di rumah sakit di Indonesia melaporkan bahwa Pseudomonas aeruginosa telah resisten sebesar 60,9 % terhadap ceftriaxone sedangkan Klabsiella pneumonia resisten sebesar 75,7 % (Radji, Fauziah, & Aribinuko, 2011).…”
Section: Pendahuluanunclassified